Alternative Approaches Used by People to Induce Sleep: Insights from a Social Media Survey - Sexton-Radek, Kathy; Pendle, Renata; Marvi, Fatema; Larr, Abby (Disease and Health: Research Developments Vol. 3, 2025)
Inadequate sleep has a negative association with general health and well-being. Sleep is essential for adequate immune, metabolic, and endocrine functioning and may have an association with the healing of some illnesses. Sleep medicine has been considered a worldwide perspective to investigate and treat sleep disturbances and disorders. Large-scale epidemiological studies along with World Health Organization-sponsored studies using the International Classification of Functioning, Disability and Health System, have categorized patient complaints about their sleep. The aim of the study was to identify some of the sleep onset practices which may or may not include a treatment for sleep onset. The severity and treatment needs of sleep disorders have been underscored. The current study was designed as a survey investigation of an aspect of a common patient sleep complaint—difficulty falling asleep. A social media approach was used to capture the comments about sleep from individuals responding to a Facebook questionnaire. The questionnaire was in English and Portuguese (per the second author). The individual responses were from 12 countries/6 continents. Sleep disturbances were reported to range from 2 to 18 months: initiating sleep difficulty 16 months history on average, Disrupted sleep at an eleven-month length on average, Sleep maintenance at a fifteen-month length on average and non-restorative sleep at an eighteen-month length on average. Modal responses in terms of alternative medicine use and daytime practices to promote sleep are represented.